THE NEW ATLANTEANS: FORCED MIGRATION, STATELESSNESS AND JUSTICE - Magnus Arni Skjöld MAGNUSSON; Heather ALLANSDÓTTIR; Danielle Elizabeth BEAUCHEMIN; Elham FAKOURI; Judit RODRIGUEZ; Anca TĂNASIE (Management & Marketing)
With the well-documented predicted continuation of rising sea-levels as a result of man-made climate change over the next century, two interrelated issues have emerged in international law and global policy discussions: what to do about both those who are displaced due to climate change, those whose homelands are entirely physically eradicated due to climate change, and those whose homelands remain geographically/ physically intact but who nonetheless experience forced migrations, and what transnational duties exist in both cases. This article will explore the interrelated but separate nature of these two issues, and the salient features of appropriate transnational responses, particularly the gendered dimensions of forced migration in both cases. It builds upon the existing literature of statelessness, forced migration, displacement and gendered aspects of the transnational obligations in all of these, whilst forging new ground by advancing a new thesis for how the twentieth-century paradigms of forced migration and statelessness must be modified in the wake of this new reality, of climate-crisis-induced forced migration and statelessness.